Analisis Dan Perancangan Knowledge Management System Berbasis Web Pada PT Metrindo - Pranata, Yoga; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2021)
The development of information technology has changed human lifestyles where information is more easily accessed and disseminated via the internet, as are many benefits that we can feel with the internet but it also has a negative impact with the amount of information that can cause us to misunderstand information or differences information between one party and another party. Knowledge Management helps us manage knowledge so that existing knowledge can be disclosed, stored and distributed to those in need. Knowledge is divided into 2: knowledge that is difficult to express or express (tacit) and knowledge that can be expressed or expressed (explicit) and often important knowledge takes the form of tacit as it relates to feelings, art, physical abilities. So we need a method that can convert between knowledge, the SECI Model is Socialization changing tacit knowledge into tacit, Externalization changing tacit knowledge to explicit, Combination changing explicit knowledge to explicit, and Internalization changing explicit knowledge to tacit knowledge.